Evidence for Single-Type Semantics—An Alternative To $e$/$t$-Based Dual-Type Semantics. (15th August 2018) - Liefke, Kristina; Werning, Markus
Abstract: Partee (2009) conjectures a formal semantics for natural language (hereafter, single-type semantics ) that interprets CPs and referential DPs in the same semantic type: properties of situations. Partee's semantics contrasts with Montague semantics and its recent contenders (dubbed dual - or multi-type semantics ) which assume distinct basic types for the semantic values of referential DPs (i.e. individuals) and CPs (i.e. propositions, truth-values, or sets of assignment functions). Partee's conjecture is motivated by results in event semantics and discourse representation theory, which support the indirect uni-directional shiftability between propositions and individuals. However, none of these results supports the identity of the types for individuals and propositions. Our paper improves upon the strength and scope of Partee's support for single-type semantics. In particular, it identifies a number of new arguments for the adoption of single-type semantics which display this semantics' greater unificatory and explanatory power. These arguments are based on the ability of single-type semantics to provide a uniform account of the distributional similarities between DPs and CPs, to explain the truth-evaluability of DP fragments, and to capture semantic inclusion relations between CPs and referential DPs. To further support single-type semantics, we defend it against a number of objections.